14-year case series of eyelid sebaceous gland carcinoma in Chinese patients and review of management - Lam, Stacey C; Li, Emmy Y M; Yuen, Hunter K L (British journal of ophthalmology, 2018)
AimsSebaceous gland carcinoma (SGC) of the eyelid is a rare but potentially deadly cancer. The purpose of this study was to determine whether the American Joint Committee on Cancer (AJCC) 7th Edition T category for SGC correlated with metastasis and survival in the Chinese population.MethodsThis was a retrospective, single-centre cohort study. Patients with surgically resected eyelid SGC between January 2001 and May 2015 at the Hong Kong Eye Hospital were reviewed. Tumours were staged using the AJCC criteria. The main outcome measures included local recurrence, metastasis and death. Disease-free survival (DFS) was measured from the completion of treatment; overall survival was measured from the date of initial diagnosis.ResultsThe study included 22 Chinese patients with a mean age of 65.4 years. The majority presented as a nodular lesion (91%) with 12 eyes (54.5%) initially misdiagnosed and a mean presentation time of 1 year. It was found that those with AJCC stage T2b or higher were significantly associated with lymph node metastasis (P=0.002) when compared with those with stage T2a. Older age at diagnosis (P=0.035) and no misdiagnosis (P=0.025) were associated with shorter DFS. Those with stage 3a or higher were associated with shorter DFS (P=0.007) and overall survival (P=0.024).ConclusionSimilar to previous reports, in this Chinese cohort, AJCC staging for SGC correlated with lymph node metastasis, DFS and overall survival. Those with stage 2b or higher on presentation will need closer surveillance for lymph node metastasis and may benefit from sentinel lymph node biopsy.